Application of knowledge-based system in automated data warehouse design - Sitompul, Opim Salim; Mohd Noah, Shahrul Azman (2004)
Data warehouse has become more and more popular for an enterprise as a data repository system.Yet tools to appropriately design its conceptual model are rarely available, even though this model is known as a key for the successful of the overall design. In this paper we propose an approach and a tool to guide the decision makers in designing data warehouse conceptual model based on the Entity Relationship (ER) model of the existing operational database systems. Using this approach, the ER model is automatically transformed into the multidimensional model.